Dosimetric Comparison of Intensity-Modulated Radiation Therapy (IMRT) and Volumetric-Modulated Arc Therapy (VMAT) for Synchronous Bilateral Breast Cancer Irradiation: A Planning Study - Thakur, Niketa; Kaur, Harkirat; Kaur, Supreet; Sharma, Ramita; Lehal, Priyanka; Sharma, Abhishek (Asian Pacific Journal of Cancer Care, 2024)
Background and objective: The large radiation field and surrounding normal structures in synchronous bilateral breast cancer (SBBC) make treatment planning and dose delivery significantly more challenging than in unilateral breast cancer. Intensity-modulated radiation therapy (IMRT) and volumetric-modulated arc therapy (VMAT) have the potential to improve target dose coverage while minimizing normal tissue exposure compared to 3D-conformal radiotherapy (3D-CRT). This study aimed to investigate the dosimetric variations of IMRT and VMAT techniques using a single isocenter for planning SBBC cases. Material and methods: Five patients who had undergone bilateral mastectomy were included in this study. A dose of 50 Gy in 25 fractions was prescribed. VMAT and IMRT plans were created for each patient using a mono-isocentric approach. Dosimetric data for the target volume (PTV) and organs at risk (OARs) were compared. Results: VMAT plans demonstrated a trend towards better PTV coverage compared to IMRT (V95 IMRT = 94.8720, V95 VMAT = 95.8740; P = 0.316). VMAT plans significantly improved dose homogeneity, with a decrease in V105% from 2.886% to 0.312% (P = 0.001). IMRT plans showed a trend towards higher lung mean dose (Dmean) and V20Gy compared to VMAT plans. The irradiation dose to the heart was significantly higher in the IMRT plans compared to VMAT plans, resulting in a higher Dmean (15.836 Gy vs 13.580 Gy; P = 0.026), V25Gy (16.498% vs 13.832%; P = 0.046), and V30Gy (9.774% vs 7.022%; P = 0.043). Conclusion: The single-isocentric VMAT technique is a convenient approach for SBBC planning, improving target volume coverage with optimal normal tissue sparing. It is a feasible option for synchronous bilateral breast irradiation.